Acute myocardial infarction in a 35–year–old man with coronary artery aneurysm most probably caused by Kawasaki disease - Saeed Alipour Parsa (Asian Pacific Journal of Tropical Biomedicine, 2014)
We present a 35-year-old man with history of Kawasaki disease who referred with myocardial infarction, and angiography, revealing aneurysm of left main and left anterior descending coronary arteries. The patient underwent percutaneous coronary intervention and thrombectomy and was discharged after 6 d. Coronary artery sequels of Kawasaki disease should be considered as one of the underlying causes of acute myocardial infarction in young adults.